Diagnostic dilemma of a case of sigmoid volvulus complicating pregnancy - Nur Azurah AG; Ani Amelia Z; Sagap I (Department of Surgery, UKM Medical Centre, 2011)
We report the case of a 34-year-old Malay, admitted for constipation and abdominal pain at 35 weeks of gestation. Initially, she was diagnosed to have paralytic ileus and was managed conservatively. As her condition did not improve, emergency laparotomy was performed for suspected intestinal obstruction. She delivered a baby boy weighing 2.84kg with good Apgar score through a caesarean section. Intra-operatively, she was noted to have sigmoid volvulus and sigmoidopexy was performed. Post-partum, colonoscopy and bowel decompression was performed. She recovered well and was discharged on day 5. This case illustrates the need to diagnose or suspect volvulus in pregnant woman presenting with severe constipation as early surgical intervention can reduce morbidity to both mother and fetus.